Mid- and long-term effects of family constellation seminars in a general population sample: 8- and 12-month follow-up - Hunger-Schoppe, Christina; Weinhold, Jan; Bornhäuser, Annette; Link, Leoni; Schweitzer, Jochen (Family process, 2015)
In a previous randomized controlled trial (RCT), short-term efficacy of family constellation seminars (FCSs) in a general population sample was demonstrated. In this article, we examined mid- and long-term stability of these effects. Participants were 104 adults (M = 47 years; SD = 9; 84% female) who were part of the intervention group in the original RCT (3-day FCS; 64 active participants and 40 observing participants). FCSs were carried out according to manuals. It was predicted that FCSs would improve psychological functioning (Outcome Questionnaire OQ-45.2) at 8- and 12-month follow-up. Additionally, we assessed the effects of FCSs on psychological distress, motivational incongruence, individuals’ experience in their personal social systems, and overall goal attainment. Participants yielded significant improvement in psychological functioning (d = 0.41 at 8-month follow-up, p = .000; d = 0.40 at 12-month follow-up, p = .000). Results were confirmed for psychological distress, motivational incongruence, the participants’ experience in their personal social systems, and overall goal attainment. No adverse events were reported. This study provides first evidence for the mid- and long-term efficacy of FCSs in a nonclinical population. The implications of the findings are discussed.
First published: 29 September 2014
Gesehen am 04.08.2020